2011
DOI: 10.1242/jcs.075770
|View full text |Cite
|
Sign up to set email alerts
|

TNFα-induced noncanonical NF-κB activation is attenuated by RIP1 through stabilization of TRAF2

Abstract: The current paradigm of noncanonical NF-κB signaling suggests that the loss of TRAF2, TRAF3 or cIAP1 and cIAP2 leads to stabilization of NF-κB-inducing kinase (NIK) to activate the noncanonical pathway. Although a crucial role of RIP1 in the TNFα-induced canonical NF-κB pathway has been well established, its involvement in noncanonical activation of NF-κB through the TNFR1 receptor, is unknown. Here we show that TNFα is capable of activating the noncanonical NF-κB pathway, but that activation of this pathway i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 57 publications
3
39
1
Order By: Relevance
“…In the latter study, activation of RIP1 was shown to render it a target for caspase 8, generating RIP1 fragments that inhibited IRF3 signaling (23). Our data raise the possibility that inhibitory actions of RIP1 may extend to both the IRF3-and NF-B-dependent components of signaling responses to poly(I·C) through mechanisms as yet uncharacterized but potentially involving potentiation of signaling via noncanonical NF-B (13).…”
Section: Figmentioning
confidence: 59%
See 1 more Smart Citation
“…In the latter study, activation of RIP1 was shown to render it a target for caspase 8, generating RIP1 fragments that inhibited IRF3 signaling (23). Our data raise the possibility that inhibitory actions of RIP1 may extend to both the IRF3-and NF-B-dependent components of signaling responses to poly(I·C) through mechanisms as yet uncharacterized but potentially involving potentiation of signaling via noncanonical NF-B (13).…”
Section: Figmentioning
confidence: 59%
“…While these data indicate that RIP1 lies within the pathways regulating responses to poly(I·C) in primary airway epithelial cells, it does not identify the point in the signaling pathways that is regulated by Pellino-1. Although RIP1 is usually thought to be involved in activation of NF-B signaling via interaction with the TRIF signaling pathway (5,17) and IKK complex (13), we note that RIP1 has also been shown very recently to negatively regulate activation of noncanonical NF-B by TNF-␣ signaling (13) and also to negatively regulate the IFR3 induction downstream of RIG-I activation (23). In the latter study, activation of RIP1 was shown to render it a target for caspase 8, generating RIP1 fragments that inhibited IRF3 signaling (23).…”
Section: Figmentioning
confidence: 85%
“…It also is possible that hematopoietic RIPK1 deficiency stimulates the degradation of prosurvival proteins cIAP1/2 and TRAF2, thereby making cell death more likely. In addition to mediating survival, the IAPs have been shown to regulate TNF production; thus RIPK1 deficiency may promote cell death and induce inflammation via effects on cIAP1/2 protein stability (40)(41)(42). Increased chemokine and cytokine production also are features associated with the rapid HSPC death observed in the RosaCreER…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, TNF-a, an agonist of the classical NF-kB pathway, has been shown to activate the alternative NF-kB pathway in murine embryonic fibroblasts (34,35). These findings demonstrate that multiple ligands previously considered as unique activators of either classical or alternative NF-kB can indeed activate both pathways.…”
Section: Discussionmentioning
confidence: 99%